TAHLILAN SEBAGAI SINKRONISASI AGAMA DAN BUDAYA: (Perspektif Legal Maxim) - Annisa, Firda (Universitas Darunnajah Jakarta, Indonesia, 2022)
Before Islam came, the majority of Indonesian people at that time are still Hinduism. Then Walisongo came to bring Islam and started to spread Islam doctrines in order to call the Indonesian who at that time were still keep up with Hindu doctrines, one of their doctrine called